Study of CdTe film growth by CSS on three different types of CdS coated substrates. (2018) - Raza, M. Taslim; Rahman, M. Zishanur; Reyaz, M.; Karim, Mohammad Rezaul
Abstract: CdTe (cadmium telluride) is a very useful material for various applications such as in solar cell fabrication, electro-optical modulators, radiation detectors etc.. It is one of the cost effective and suitable material for thin film solar cells production due to its ease of thin film fabrication, high absorption coefficient and ideal band gap. CSS (close spaced sublimation) is one of the suitable technologies of CdTe thin film fabrication for various applications. In this study, close spaced sublimation of CdTe for its deposition on CdS (cadmium sulfide) coated glass was performed using a custom-designed CSS system for solar cell application. The deposition characteristics of CdTe was studied on three types of CdS layer. First CdS layer was obtained by sputtering technique, and second CdS layer was obtained by CBD (chemical bath deposition) technique. And third CdS layer was CdS:O (oxygenated nanocrystalline CdS film). The surface morphology was studied using FESEM (field emission scanning electron microscope). The XRD was done to confirm the crystal details of the film. UV-VIS spectrophotometer was used for optical absorption and transmission characteristics of the film which was further used to calculate the band gap of the deposited film. The thickness of the film was measured using DektakXT, Bruker profilometer. Results of current study show that (a) the close spaced sublimation technique for CdTe deposition is very consistent irrespective of the quality of substrate used, (b) the pin hole free uniform films are obtained in all three types of CdS substrates used (c) little deviation in CdS:O substrate is seen as the transmission characteristic is concerned. The band gap gets closer to the theoretical value